The Difference of Average Mean Platelet Volume (MPV) Values in Stable Angina Pectoris Patients with Symptoms of Depression and without Symptoms of Depression - Arief Wibawa; Agus Siswanto; Hariadi Hariawan (Faculty of Medicine Universitas Gadjah Mada, 2015)
Background: Depression is an independent predictor of cardiovascular events. Increased platelet reactivity is one of several possible mechanisms proposed to explain the relationship between psychosocial factors to coronary heart disease. Mean platelet volume (MPV) is an indicator of platelet activation. MPV associated with major cardiovascular events in coronary heart disease.Objective: This study aimed to determine the average difference of mean platelet volume (MPV) in stable angina pectoris patients with symptoms of depression and without symptoms of depression.Methods: The study design was a cross-sectional study. Sampling was carried out in sequence from Stable Angina Pectoris patients who were treated in the internal medicine department of Dr. Sardjito hospital Yogyakarta. MPV and HAD score were measured once on admission. Data presented as a descriptive analysis of the subjects' characteristics on average and standard deviation. The difference average of MPVbetween Stable Angina Pectoris patients with symptoms, depression and without symptoms depression assessed with Pearson's correlation. The results were considered at the signifi cance level of p <0.05.Results: There were 40 subjects, consisting of 20 Stable Angina Pectoris patients with symptoms, depression and 20 Stable Angina Pectoris without symptoms depression. The difference average of MPV in this study was 7.56 ± 0.95 fl . Average MPV in Stable Angina Pectoris patients with symptoms depression was 8.45 ± 0.82 fl and without symptoms depression was 7.68 ± 0.99 fl with p = 0.009.Conclusion: In this study, there was a statistically signifi cant difference of average MPV values in stable angina pectoris patients with symptoms of depression and patients without symptoms of depression.